Researching Ideologies Using Discourse Analysis: A Case Of Bakun Hydroelectric Public Controversy Study. - Hussein, Adnan; Hj. Siarap, Kamaliah (2005)

(untitled)
This paper essentially is our reflections and assessment of our own study of Bakun Hydro Electric Project which was conducted in 200-2003. Our discussion will focus on specifically on methodological perspectives that we have employed in conducting our study - discourse analysis. However, it should noted a the outset that the study was not about environmental discourse, although it does contain discourse on environment. The study was more concerned on the public controversy and examined the ideological forces behind the debates.